Simulated anthropogenic carbon and CFC-12 with the NEMO model using the perturbation approach - Terhaar, Jens; Tanhua, Toste; Stöven, Tim; Orr, James C; Bopp, Laurent (SEANOE, 2020)
This dataset provides simulated monthly averaged ocean temperature, salinity, CFC-12, and anthropogenic carbon in August 2005 from NEMO simulations with the ORCA2 and ORCA025 configurations. Anthropogenic carbon was calculated using the perturbation approach by Sarmiento et al. [1992]. For ORCA2, simulated CFC-12 and anthropogenic carbon is also provided for August 2100.